Selling transracial adoption : families, markets, and the color line - Raleigh, Elizabeth Yoon Hwa, 1977- (Temple University Press, 2018)
While focused on serving children and families, the adoption industry must also generate sufficient revenue to cover an agency's operating costs. With its fee-for-service model, Elizabeth Raleigh asks, How does private adoption operate as a marketplace? Her eye-opening book, Selling Transracial Adoption, provides a fine-grained analysis of the business decisions in the adoption industry and what it teaches us about notions of kinship and race. Adoption providers, Raleigh declares, are often tasked with pitching the idea of transracial adoption to their mostly white clientele. But not all children are equally "desirable," and transracial adoption-a market calculation-is hardly colorblind. Selling Transracial Adoption explicitly focuses on adoption providers and employs candid interviews with adoption workers, social workers, attorneys, and counselors, as well as observations from adoption conferences and information seto illustratelustrate how agencies institute a racial hierarchy-especially when the supply of young and healthy infants is on the decline. Ultimately, Raleigh discovers that the racialized practices in private adoption serve as a powerful reflection of race in America